UJI AKTIVITAS ANTIOKSIDAN SENYAWA METABOLIT SEKUNDER DARI EKSTRAK KULIT BATANG PALIASA (Kleinhovia hospita Linn) - Imran; Angga Febrian; Zainal Syam Arifin; Thamrin Azis; I Wayan Sutapa; Nohong; La Agusu; Syahrir; Alwahab (Jurnal Analis Kesehatan Kendari, 2025)
This study aims to test the antioxidant activity of secondary metabolite compounds contained in paliasa (Kleinhovia hospita Linn) stem bark extract. This plant is traditionally known to have health benefits, but research on the antioxidant activity of its stem bark is still limited. Extraction was done using a maceration method using a methanol solvent, followed by liquid-liquid fractionation using n-hexane and ethyl acetate to separate compounds based on their polarity. Phytochemical screening showed that the n-hexane fraction contained alkaloids and terpenoids, while the ethyl acetate fraction contained alkaloids, flavonoids, tannins, and saponins. The antioxidant activity of both fractions was tested using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method with absorbance measurements at a wavelength of 517 nm. The test results showed that the ethyl acetate fraction had an IC50 value of 51.7687 ppm, while the n-hexane fraction had an IC50 value of 60.5442 ppm. Based on the classification of antioxidant activity, both fractions are categorized as strong antioxidants (IC50 between 50-100 ppm). For comparison, vitamin C has an IC50 value of 14.3421 ppm, indicating strong antioxidant activity. The results of this study indicate that paliasa bark extract, especially the ethyl acetate fraction, has the potential as a source of natural antioxidants that can be further developed in the pharmaceutical, cosmetic, and food industries as an alternative to synthetic antioxidants with toxicity risks.